The Effect of Salinity on Osmoregulation Physiology of Survival and Respiration Rate of Tilapia Fish (Oreochromis niloticus) - Merta, I Wayan; Kusmiyati, Kusmiyati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Osmoregulation is a process used by fish to maintain the balance of water and ion levels in the body, so that salinity becomes a limiting factor for the life of Tilapia fish. This study aims to determine the effect of salinity on osmoregulation, physiological survival and respiration rate of Tilapia fish (Oreochromis niloticus). This research design used an experimental method with a Completely Randomized Design (CRD) approach. This research design involved four different treatment levels and was carried out with five repetitions for each treatment. Each treatment was designed to test the effect of a particular variable on the observed parameters, with repetitions aimed at ensuring consistency of results. P1: Control (No Filter). P2: Salinity 5 ppt. P3: Salinity 10 ppt. P4: Salinity 15 ppt. The activity of tilapia in each salinity medium was observed to determine changes in behavior after the fish were inserted into the salinity medium. Physiological responses were observed, and the respiration of tilapia through operculum movements in each salinity medium was calculated after 5 minutes of treatment for 1 minute. Survival was calculated after 5 minutes of treatment until the tilapia died. Data were analyzed using one-way ANOVA, with a significance level of 5%. If there was a significant difference, it was continued with the LSD test (Least Significant Difference). Based on the ANOVA test, the Sig. value obtained was .000 (<0.05), indicating that there is an effect of salinity on the physiological osmoregulation of tilapia survival (Oreochromis niloticus). Based on the results of the Multiple 12 Comparisons LSD test, it can be seen that all differences between treatment groups are significant with a 95% confidence level (p < 0.05). Based on data analysis and discussion, the study concluded that salinity has a significant effect on the respiratory rate of tilapia (Oreochromis niloticus), where increasing salt levels cause an increase in the frequency of operculum movements in response to osmotic stress. The main factors affecting the survival of tilapia to salinity differences are the ability to osmoregulate, which is increasingly inhibited as salt levels increase, as well as the duration of exposure to more hypertonic environmental conditions.